Resíduos da construção civil: um olhar a partir da «prancheta» - Meira, Flora Alexandre (2011)
The construction industry plays an important role in the Brazilian socioeconomic context. On the other hand, its activity is recognized as one of the most impactful to the environment, whether the high consumption of natural resources that it requires, either by habitat modification, or the generation of waste. Since the 1990s the high rates of construction waste generation are discussed by researchers. However, when dealing with the minimization of generation of construction wast, the predominant discourse is focused on waste management actions at the construction site or alternatives for recycling and / or reuse of the construction waste. The theme of this research takes a fresh look on this issue, proposing to identify the relationship between the design process of Vertical Multi-Family Housing and the generation of Construction Waste, from a qualitative analysis of the design process of an architecture firm with extensive experience in the development of this kind project. The results point to some design elements that can be crucial for the generation of construction wast, such as structure, masonry and its interface with electrical and hydraulic installations and finishing. In addition, were identified some actions that, when adopted in design process, may favor the minimization of construction waste: standardization of components and dimensions and optimization of coordination and detailed design process. As regards the attitude of the professionals interviewed, it was noticed that despite having shown little knowledge about the residue of the subject, adopted in their projects principles of rationalization of construction which indirectly influence the reduction of construction waste. The main contribution of this research is approaching the theme of the construction waste generation of the architecture research lines.